Changes in Mortality and Cerebral Palsy in Extremely Low-Birth-Weight Infants in a Tertiary Center in Hong Kong. (January 2020) - Chee, Yuet Yee; Wong, Rosanna Ming Sum; Wong, Mabel Siu Chun; Tso, Winnie Wan Yee; Wong, Wilfred Hing Sang; Lee, So Lun
Introduction . We retrospectively reviewed a cohort of extremely low-birth-weight (ELBW) babies born at Queen Mary Hospital and explored if there is any time trend in survival and short-term neurodevelopmental outcomes. Methods . We included ELBW infants born at Queen Mary Hospital between 2008 and 2015. The relationships between multiple risk factors with survival and neurodevelopmental outcomes were analyzed by either Cox regression or univariate logistic regression analysis. We also compared this birth-year period with our previous study from 1993 to 2002. Results . Two hundred seventeen ELBW infants were delivered during the study period. There was significantly higher overall survival rate (81.1%) in 2008 to 2015 compared with 71.4% in 1993 to 2002. One hundred forty-three out of 176 (81%) survivors were assessed at a corrected mean age of 18.1 months. A total of 4.2% had cerebral palsy. There were significantly lower rates of cerebral palsy in 2008 to 2015 (4.2%) compared with 1993 to 2002 (13.5%). Conclusions . We showed a temporal improvement in survival and short-term neurodevelopmental outcomes.